(untitled) (Ius Novum, 2024)
IN THE 21st century, many pieces of legislation are moving away from basing the features of the crime of rape on the use of various types of coercion and replacing it with the violation of the will of the injured person. The aim of the article, which is of an analytical nature, is to indicate a change in the understanding of the features of a crime under Art. 197 of the Penal Code and its adaptation to the current awareness and views of society. This issue is relatively absent in scientific discussions, which is probably due to the fact that only recently has attention been paid to certain phenomena, such as stealthing. The authors thesis that in view of the current interpretation of the features of the crime of rape, presented both in the doctrine and case law, the current legal status meets the criteria of Art. 36 of the Istanbul Convention, while the doctrine and jurisprudence, and perhaps even the legislator, face the task of adapting the crime of rape to contemporary needs. The conclusions drawn on the basis of the research conducted show problems that are only mentioned in criminal law literature.